A facile approach to synthesize 3, 5-disubstituted-1, 2, 4-oxadiazoles via copper-catalyzed-cascade annulation of amidines and methylarenes1. Issue 42 (25th May 2015) - Guo, Wei; Huang, Kunbo; Ji, Fanghua; Wu, Wanqing; Jiang, Huanfeng
<x xml:space="preserve">Abstract</x> A tandem Cu-catalyzed oxidation–amination–cyclization reaction for synthesizing various 3, 5-disubstituted-1, 2, 4-oxadiazoles from easily available amidines and methylarenes or methylhetarenes is reported.